2012
DOI: 10.1371/journal.ppat.1002605
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mouse Model of Schistosoma haematobium Egg-Induced Immunopathology

Abstract: Schistosoma haematobium is the etiologic agent for urogenital schistosomiasis, a major source of morbidity and mortality for more than 112 million people worldwide. Infection with S. haematobium results in a variety of immunopathologic sequelae caused by parasite oviposition within the urinary tract, which drives inflammation, hematuria, fibrosis, bladder dysfunction, and increased susceptibility to urothelial carcinoma. While humans readily develop urogenital schistosomiasis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(173 citation statements)
references
References 65 publications
9
161
1
2
Order By: Relevance
“…Thus granulomata protect the host from toxic products of schistosome eggs. Despite the importance of this phenomenon in schistosomiasis mansoni, until recently (Fu et al, 2012), an informative model to analyse the issue in the context of S. haematobium SEA was not available. We aim to carry out studies in the future to address this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus granulomata protect the host from toxic products of schistosome eggs. Despite the importance of this phenomenon in schistosomiasis mansoni, until recently (Fu et al, 2012), an informative model to analyse the issue in the context of S. haematobium SEA was not available. We aim to carry out studies in the future to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Such a decline in the pattern of this infection suggests the importance of schistosome-associated bladder cancer that, elsewhere, may be more widespread than is presently thought (Shiff et al, 2010). In recent progress on the understanding of the host-parasite relationship of schistosomiasis haematobia, a draft genome sequence for S. haematobium was reported (Young et al, 2012) and a mouse model of S. haematobium egg induced immuno-pathogenesis and fibrosis typically found in human urogenital schistosomiasis was described (Fu et al, 2012). It was recently reported that this schistosome is amenable to being cultured in vitro and transformed with nucleic acid probes.…”
Section: Introductionmentioning
confidence: 99%
“…The main human-infecting species are S. mansoni (in Africa and South America) and S. japonicum (in South and East Asia), causing intestinal and hepatosplenic schistosomiasis, and S. haematobium (in Africa and Middle East), causing urinary schistosomiasis. The latter species accounts for nearly half of that number, but little is known about the mechanisms underlying its pathophysiology, primarily due to the lack of an experimentally tractable mouse model [15]. These parasites are responsible for the most common fibrotic disease that arises due to chronic inflammation and the scarring of (liver or bladder) tissue.…”
Section: Schistosomiasismentioning
confidence: 99%
“…Here, we provide an overview of the mechanisms by which clinically important parasites -such as Schistosoma mansoni and S. japonicum, and hydatid cysts from Echinococcus multilocularis that localize primarily in the liverdrive liver fibrogenesis following their interaction with myeloid cell subsets. Other parasites, such as Trypanosoma cruzi , Taenia solium, Nippostrongylus brasiliensis and Schistosoma haematobium, inducing fibrosis in the heart, brain, lungs and bladder, respectively [9][10][11][12][13][14][15], and liver flukes, such as Clonorchis sinensis and Opisthorchis viverrini , causing bile periductal fibrosis, which increases the risk for cholangiocarcinoma [16][17][18][19][20], are not covered here, due to the marginal information on the phenotype, function and activation status of myeloid cells in these pathogenic processes.…”
Section: Introductionmentioning
confidence: 99%
“…In female genital organs, ovaries and fallopian tubes sometimes have high egg burdens, but the mean eggs burdens in autopsy series are low. Egg burdens of the uterus and vagina are even lower 2,3 . The aim of this study is to report a case of schistosomiasis of the abdominal cavity and infertility.…”
Section: Introductionmentioning
confidence: 99%